2022
DOI: 10.1002/pat.5874
|View full text |Cite
|
Sign up to set email alerts
|

Thermosensitive acetylated carboxymethyl chitosan gel depot systems sustained release caffeic acid phenethyl ester for periodontitis treatment

Abstract: Periodontitis is a chronic inflammatory disease of tooth support tissues leading to progressive destruction of periodontal soft tissues as well as alveolar bone, and can be treated with anti‐inflammatory and bone‐protective agents to prevent disease progression. Caffeic acid phenethyl ester (CAPE) is a natural polyphenolic compound with anti‐inflammation, anti‐oxidation and bone tissue repair efficacy. In this work, we synthesized a thermosensitive hydrogel matrix of acetylated carboxymethyl chitosan (A‐CC), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Peng et al employed N-acetylation to create an acetylated carboxymethyl CS for inclusion into an intelligent hydrogel for periodontal therapy. His research revealed that by varying the level of acetylation of the carboxymethyl CS hydrogels, the gelation temperature could be adjusted ( Peng et al, 2023 ). The gel formation temperature was 36.9°C when the extent of acetylation was 63.9%, and 33.2°C when the percentage of acetylation was 85.3%.…”
Section: Biomaterials Used To Construct Injectable Thermosensitive Hy...mentioning
confidence: 99%
“…Peng et al employed N-acetylation to create an acetylated carboxymethyl CS for inclusion into an intelligent hydrogel for periodontal therapy. His research revealed that by varying the level of acetylation of the carboxymethyl CS hydrogels, the gelation temperature could be adjusted ( Peng et al, 2023 ). The gel formation temperature was 36.9°C when the extent of acetylation was 63.9%, and 33.2°C when the percentage of acetylation was 85.3%.…”
Section: Biomaterials Used To Construct Injectable Thermosensitive Hy...mentioning
confidence: 99%
“…Caffeic acid phenethyl ester (CAPE) is a polyphenolic natural substance with anti-inflammatory, antioxidant and bone defect repair effects. Pen et al [ 100 ] synthesized a thermosensitive hydrogel matrix of acetylated carboxymethyl chitosan (A-CS) and applied it for the first time for topical periodontal administration. Compared with conventional systemic drug delivery, the CAPE-loaded A-CS hydrogel (CAPE-A-CS) has the superiority of in situ drug reservoir formation, slow release and precise enhancement of drug concentration at the lesion site.…”
Section: Biomaterials Regulate Macrophage Polarizationmentioning
confidence: 99%
“…Injectable chitosan-based hydrogels have had promising applications in the field of drug delivery because they become gelling matrices at the injection site, and they can release drugs in a controlled manner [ 44 , 172 , 173 , 175 ]. The hydrogel is used to treat periodontitis by forming a depot, allowing for a sustained release of caffeic acid phenethyl ester in the lesion sites [ 173 ]. The thermosensitive hydrogel matrix, made of acetylated CMC, effectively inhibits inflammation and promotes bone tissue repair in periodontitis therapy.…”
Section: Pharmaceutical and Biomedical Applications Of Chitosan-based...mentioning
confidence: 99%